Prevalence and Factor Assessment of Helicobacter pylori Infection in a Rural Setting: Life Sciences-Microbiology for health care - Jaiswal1, Suresh; Tiwari, Bishnu Raj; Sharma, Dinesh C (International Journal of Life Science and Pharma Research, 2021)
Helicobacter pylori, is a spiral-shaped pathogenic bacterium which is believed to cause peptic ulcers, chronic gastritis, active ulcers disease and many gastrointestinal diseases. The study aimed to find out the prevalence of H. pylori infection and factors associated with the infection in a rural setting of Nepal. A cross-sectional study was conducted among 804 participants from March 2019 to April 2020 in a rural setting of Province 2, Nepal. A structured questionnaire was administered to obtain information about the socio-demographic condition, food habits, hygienic practices, and family history. Venous blood was collected for laboratory examination of H. pylori antibodies.Serum anti-H. Pylori antibodies were detected; out of 804 participants 375 (46.6%) were positive for H. pylori infection; 411(51.1%) were female and male 393 (48.9%). The minimum age of the participant was 13, the maximum was 85 with a mean age of 43±15.26. A significant association was found with age group Pvalue 0.012, with religion [P-value 0.021 and OR (95% CI) was 2.938 (1.128-7.650)] and place of residence [P value 0.011 OR (95% CI) was 1.438(1.087-1.904)]. A significant association was also observed with marital status, occupation, total family members and total annual income. A significant association was seen with food habits like consumption of vegetables, onion and garlic, milk and meat products, spicy foods, and fried foods.Even though the prevalence of H. pylori is lower than other still has a higher prevalence than developed countries in the rural area and socio-demographic factors and food habit are associated with H. pylori. Awareness campaigns should be focused on rural areas where education is not primary.